Pathological characteristics and genetic features of melanin-producing medullary thyroid carcinoma - Changsong Wang; Tian Yun; Zhicheng Wang; Nianlong Meng; Naijun Fan; Xuexia Lv; Fulin Li (BMC, 2018)
Abstract Objective To study the clinicopathological characteristics and genetic features of melanin-producing medullary thyroid carcinoma (MP-MTC). Methods The immunophenotype of MP-MTC was studied using the immunohistochemical method, and its genetic features were assayed using an amplification refractory mutation system or PCR method. Results A 71-year-old man presented with a slowly growing 5-cm mass on the left side of the neck for approximately two months. The cut surface of the neoplasm was brown and black. Melanin was found in the cytoplasm of tumor cells or the extracellular matrix. The tumor cells were positive for AE1/AE3, S-100 protein, melan A, HMB-45, synaptophysin, calcitonin, chromogranin A, melanoma, and thyroid transcription factor-1 (TTF-1) and negative for thyroglobulin. No typical genetic features were observed in this case. The patient showed no symptoms and recurrence at 12 months after the operation. Conclusions The tumor cells of MP-MTC were positive for melanin biomarkers, TTF-1 and exhibited no genetic features. Histopathology and immunohistochemistry of the tumor cells will aid accurate diagnosis.